ANALISIS KANDUNGAN FORMALIN PADA IKAN KERING DI PASAR TANJONGE SENGKANG KABUPATEN WAJO - Abidin, Zainal; Putri, Anggi Dwi; Razak, Rais (PHARMACY UMI JOURNAL SYSTEM, 2025)
Formalin (formaldehyde) is one of the chemical compounds banned by BPOM as a preservative in food additives. This study aims to determine the content of formalin (formaldehyde) in dried fish circulating in the Tanjonge Sengkang market, Wajo Regency. The sampling method used was purposive side and the test method used was qualitative analysis method using KMnO4 reagent, Tollens, Nash, Fehling A and Fehling B and Chromic Acid. The test results using the KMnO4, Tollens, Nash, Fehling A and Fehling B reagents and Chromatophytic Acid of the nine dried fish samples did not contain formalin.